2015
DOI: 10.1016/j.clinimag.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of breast density in mammography and magnetic resonance imaging in high-risk women and women with breast cancer

Abstract: Structured Abstract Purpose To evaluate the relationship between mammographic breast density (MBD), background parenchymal enhancement (BPE), and fibroglandular tissue (FGT) in women with breast cancer (BC) and at high risk for developing BC. Methods Our institutional database was queried for patients who underwent mammography and MRI. Results 403 (85%) had BC and 72 (15%) were at high risk. MBD (p=0.0005), BPE (p<0.0001), and FGT (p=0.02) were all higher in high risk women compared to the BC group. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
3
15
0
Order By: Relevance
“…17,21,22 Although fibroglandular tissues are also enhanced on MRI, MRI allows cross-sectional contiguous slice imaging, and occult cancers can be detected on MRI using meticulous, consistent technique and image interpretation. 23,24 This is consistent with a recent prospective randomized trial for patients with extremely dense breasts which has shown better detection (fewer interval cancers) compared to mammography. 25 Thus, our results suggest that mammographic density should be considered among indications for preoperative MRI.…”
Section: Factors Associated With Detection Of Occult Cancersupporting
confidence: 86%
“…17,21,22 Although fibroglandular tissues are also enhanced on MRI, MRI allows cross-sectional contiguous slice imaging, and occult cancers can be detected on MRI using meticulous, consistent technique and image interpretation. 23,24 This is consistent with a recent prospective randomized trial for patients with extremely dense breasts which has shown better detection (fewer interval cancers) compared to mammography. 25 Thus, our results suggest that mammographic density should be considered among indications for preoperative MRI.…”
Section: Factors Associated With Detection Of Occult Cancersupporting
confidence: 86%
“…Breast MRI screening today is mainly suggested only for women with high-risk backgrounds in current international guidelines, such as those published by the European Society of Breast Imaging, the European Society of Breast Cancer Specialists, and the American College of Radiology [20] , [23] , [24] . At the same time, there are only few studies examining BPE promoting factors in high-risk populations [6] , [23] , [25] , [26] .…”
Section: Discussionmentioning
confidence: 99%
“…8,10,[12][13][14][15]21,23,26,28,[32][33][34][35][36]38,[40][41][42][43][48][49][50][51][52][53][54]57,59,61 In five studies, 11,17,19,29,44 the authors acknowledged that owing to the retrospective nature of the study, it was not possible to analyze the point of menstrual cycle, although, following institutional protocol, screening breast MRI of patients who were pre-menopausal was performed during the second week of the menstrual cycle. In a total of 14 studies, the authors stated the menstrual period.…”
Section: Quantitative Background Parenchymal Enhancement Assessmentmentioning
confidence: 99%